Influence of shear stress magnitude and direction on atherosclerotic plaque composition. Issue 10 (October 2016) - Pedrigi, Ryan M.; Mehta, Vikram V.; Bovens, Sandra M.; Mohri, Zahra; Poulsen, Christian Bo; Gsell, Willy; Tremoleda, Jordi L.; Towhidi, Leila; de Silva, Ranil; Petretto, Enrico; Krams, Rob
Abstract : The precise flow characteristics that promote different atherosclerotic plaque types remain unclear. We previously developed a blood flow-modifying cuff for ApoE −/− mice that induces the development of advanced plaques with vulnerable and stable features upstream and downstream of the cuff, respectively. Herein, we sought to test the hypothesis that changes in flow magnitude promote formation of the upstream (vulnerable) plaque, whereas altered flow direction is important for development of the downstream (stable) plaque. We instrumented ApoE −/− mice ( n  = 7) with a cuff around the left carotid artery and imaged them with micro-CT (39.6 µm resolution) eight to nine weeks after cuff placement. Computational fluid dynamics was then performed to compute six metrics that describe different aspects of atherogenic flow in terms of wall shear stress magnitude and/or direction. In a subset of four imaged animals, we performed histology to confirm the presence of advanced plaques and measure plaque length in each segment. Relative to the control artery, the region upstream of the cuff exhibited changes in shear stress magnitude only ( p  < 0.05), whereas the region downstream of the cuff exhibited changes in shear stress magnitude and direction ( p  < 0.05). These data suggest that shear stress magnitude contributes to the formation of advanced plaques with a vulnerable phenotype, whereas variations in both magnitude and direction promote the formation of plaques with stable features.